2003
DOI: 10.1103/physrevb.68.113103
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of evanescent waves in a lossy left-handed material slab

Abstract: We carry out finite-difference time-domain (FDTD) simulations, with a specially-designed boundary condition, on pure evanescent waves interacting with a lossy left-handed material (LHM) slab. Our results provide the first full-wave numerical evidence for the amplification of evanescent waves inside a LHM slab of finite absorption. The amplification is due to the interactions between the evanescent waves and the coupled surface polaritons at the two surfaces of the LHM slab and the physical process can be descr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 22 publications
3
58
0
1
Order By: Relevance
“…At ℑ(δ) = 0.01, the loss becomes so heavy that the first surface mode also weakens. The results shown here are very similar to those noticed for a slab lens [20].…”
supporting
confidence: 80%
“…At ℑ(δ) = 0.01, the loss becomes so heavy that the first surface mode also weakens. The results shown here are very similar to those noticed for a slab lens [20].…”
supporting
confidence: 80%
“…This research direction was further pushed by works of Pendry and others [4,5,[46][47][48][49][50][51][52][53][54][55][56][57][58] who showed the lens with such NIM (i.e. ǫ = µ = −1 + δ)c o u l db easuperlens whose image resolution can go beyond the usual diffraction limit.…”
Section: The Temporal Coherence Gain Of the Negative-index Superlens mentioning
confidence: 99%
“…And these beyond-limit properties give us new physical pictures and opportunities to design devices. Recently, new numerical [50,51] and theoretical Green's function [52] methods are used to understand the phenomena in such systems. But so far almost all studies are done with the strictly single-frequency sources, so that the coherent properties of EM waves (or photons) in the NIM systems have not been studied to the best of our knowledge.…”
Section: The Temporal Coherence Gain Of the Negative-index Superlens mentioning
confidence: 99%
See 1 more Smart Citation
“…However, other authors have found that the amplification of pure evanescent waves depends not only on losses, but also on the slab thickness. The final consequence could be that superlensing effect can be achieved even under the presence of small absorption [16].…”
Section: Introductionmentioning
confidence: 99%